Diallel analysis for combining ability in opium poppy (Papaver somniferum) - Singh, S P; Shukla, Sudhir; Khanna, K R (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during winter season (rabi) of 1987-88 and 1988-89 to study combining ability through diallel analysis in opium poppy (Papaver somniferum L.). Six pure genotypes ('BR 79', 'BR 88', 'IC 30', 'BR 87', 'BR 85' and 'BR 76') were analysed in a 6 X 6 diallel cross for seed yield/plant (g), opium yield/plant (mg). morphine (%), oil content (%) and other 7 contributing characters in F1 and F2 generations. Variances due to general combining ability (gca) and specific combining ability (sca) were significant for all the traits, indicating the importance of both additive and non-additive gene actions with prevalence of dominant gene effect except for plant height in F1. 'IC 30' (0.20) in F1 and 'BR 76' (0.46) in F2 were the best general combiners for seed yield/plant. Only a few good combiners for seed yield might be due to long selection pressure for opium yield rather than seed yield, which is very recent. 'BR 79' X 'BR 76', 'IC 30' x 'BR 87' and 'BR 85' X 'BR 76' were the best specific cross-combination in F1 and F2 for seed yield. The crosses having significant sea effect involved high X high, high X low and low X low combiners.